Performance management concepts, skills, and exercises - Cardy, Robert L. 1955- (M.E. Sharpe, 2011)
This comprehensive text provides an engaging examination of the entire process of performance management. It balances concepts with practical skill-based exercises, and gives readers both an understanding of performance management and the ability to manage performance. An online Instructor's Manual is available to adopters, and free PPTs are available through the author's website